Metal-organic framework-derived nanocomposites for electrocatalytic hydrogen evolution reaction. (February 2020) - Chen, Ziliang; Qing, Huilin; Zhou, Kun; Sun, Dalin; Wu, Renbing
Abstract: The rapid development of hydrogen energy is strongly dependent on the economic and efficient production of hydrogen. The electrocatalytic splitting of water to molecular hydrogen via the hydrogen evolution reaction (HER) provides an appealing solution for producing high-purity hydrogen, but low-cost and highly active electrocatalysts are required for HER. Among currently investigated HER electrocatalysts, metal-organic framework (MOF)-derived nanocomposites constructed from transition metals (TMs)/TM compounds (TMCs) and carbon materials offer extremely promising and attractive HER activities because of their unique properties, such as tunable compositions, readily regulated electronic structures, controllable morphologies, and diverse configuration. Herein, this article provides a comprehensive overview of MOF-derived nanocomposites as HER electrocatalysts for water splitting. It begins with the introduction of the fundamentals of electrocatalytic HER. Afterwards, several ingeniously designed strategies for improved MOF-derived HER electrocatalysts are meticulously summarized and discussed, with special emphasis on the component manipulation of the TMs/TMCs, carbon matrix modifications, morphology tuning and electrode configuration engineering. Finally, future perspectives on the development of these nanocomposites as HER electrocatalysts are proposed.